1982
DOI: 10.1002/cm.970020102
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin binding to F‐actin protects the F‐actin from disassembly by brain actin‐depolymerizing factor (ADF)

Abstract: Brain or muscle F-actin is rapidly depolymerized to monomeric actin in vitro by actin-depolymerizing factor, a protein isolated from chick embryo brain. Binding of muscle tropomyosin to muscle F-actin protects the F-actin from depolymerization by this factor. A 8.4/1.0 molar ratio of actin subunits to tropomyosin, achieved by incubation of the F-actin with excess tropomyosin, protects 58% of the F-actin from depolymerization by excess actin-depolymerizing factor for at least 3 hr at 25 degrees C. Thus, actin-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
170
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(179 citation statements)
references
References 34 publications
9
170
0
Order By: Relevance
“…For example, one possibility is that TM may stabilize actin filaments in noumuscle cells. This function has also been inferred from in vitro experiments which have shown that TM protects actin filaments against the severing action of gelsolin (Fattoum et al, 1983;Ishikawa et al, 1989) or the activities of brain depolymerizing factor (Bernstein and Bamburg, 1982). Other experiments have shown that the nonmuscle TMs prevent villin induced severing (Mooseker et al, 1982) or bundling of F-actin (Burgess et al, 1987), but they were unable to prevent bundling caused by 55-kD protein (Matsumura and YamashiroMatsumura, 1986).…”
mentioning
confidence: 87%
“…For example, one possibility is that TM may stabilize actin filaments in noumuscle cells. This function has also been inferred from in vitro experiments which have shown that TM protects actin filaments against the severing action of gelsolin (Fattoum et al, 1983;Ishikawa et al, 1989) or the activities of brain depolymerizing factor (Bernstein and Bamburg, 1982). Other experiments have shown that the nonmuscle TMs prevent villin induced severing (Mooseker et al, 1982) or bundling of F-actin (Burgess et al, 1987), but they were unable to prevent bundling caused by 55-kD protein (Matsumura and YamashiroMatsumura, 1986).…”
mentioning
confidence: 87%
“…Tropomyosins are coiled-coiled dimers that bind along the length of actin filaments and stabilize their structures by regulating access of the filament to other actin regulatory proteins such as gelsolin [7], Arp2/3 [8], and ADF/cofilin [9,10]. Approximately forty isoforms of tropomyosins now have been identified in rodents, and most of these are expressed in nonmuscle cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…In nonmuscle cells (which do not contain troponin), TM is associated with actin in microfilaments (28,36,50) and, although the function of TM in these filaments is not known, there is evidence suggesting that one function resides in its ability to stabilize F-actin polymers (3,13). TMs from a variety of nonmuscle sources have been characterized (9,10,14,15,17), and a distinctive feature of these nonmuscle species has been their apparent molecular weight of 30,000, significantly less than that of skeletal muscle TM, which has a molecular weight range of 34,000 to 36,000.…”
mentioning
confidence: 99%